Analysis of the influence of different initial velocities on dynamic performance of multi-layer hard target penetration process - Liu, Peng; Li, Jian; Li, Changsheng; Li, Haojie; Zhang, Jinming; Zhang, He (Frontiers in Physics, 2023)
To determine the overload characteristics of the internal system of a fuze that penetrates multilayer hard targets using different fixed-link structures, a finite element model consisting of two fixed-link structures (a compression screw and a body screw) is adopted in this paper to simulate the penetration process of a three-layer concrete target plate with corresponding initial velocities. The peak amplification coefficient and vibration coefficient are used to analyze the time-domain characteristics of the penetration process signal during segmented analysis. The extracted acceleration signals of the projectile and sensor are processed by fast Fourier transform to obtain the frequency spectrum analysis results. The simulation results show that under the same working conditions, the sensor's ability to amplify the peak acceleration of the projectile is 17.77% higher for the body screw fixed-link structure, and the average vibration coefficient is also 9.55% higher. Compared with that of the body screw fixed-link structure, the performance of the compression screw fixed-link structure is better under different initial velocity conditions. The initial penetration velocity affects mainly the amplitude of each frequency corresponding to the acceleration signals of the two fixed-link fuze structure projectiles and sensors while having a relatively small influence on the frequency distribution position.